Analisis Pengaruh E-Commerce terhadap Pedagang Konvesional Industri Mebel di Kota Pasuruan: Arifatur Rosyidah, Yuniar Rahman, Eprilia Putri Maulidyah Rahman, Enik Sulistyowati - Arifatur Rosyidah; Yuniar, Rahman; Eprilia Putri Maulidyah, Rahman; Enik, Sulistyowati (Universitas Bojonegoro, 2024)
Pasuruan City has experienced a 10.2% increase in the number of industries, with the furniture industry serving as a key driver of the local economy. The furniture sector in Pasuruan is highly developed, with production that has penetrated international markets. However, the rise of E-Commerce has rapidly transformed traditional business practices, significantly impacting conventional furniture traders in the city. This research aims to examine how E-Commerce affects these traditional traders. Using a quantitative approach, the study sampled 30 furniture business owners selected through non-probability sampling. Data was collected via a Google Form questionnaire and processed using Excel software. The findings indicate a strong and significant correlation between E-Commerce and the traditional furniture industry, showing that E-Commerce has a positive influence and offers substantial benefits to conventional furniture traders in Pasuruan City.